Ecoliteracy among Tribals in Eastern India. (February 2022) - Majumdar, Koustab; Chatterjee, Dipankar
This article is based on field research investigating levels of ecoliteracy and associating factors among four tribal groups in Jharkhand and West Bengal, involving 360 respondents from the Lodha, Santhal, Asur and Oraon communities. The study revealed low to extremely high levels of ecoliteracy and identified several specific factors as significant predictors of ecoliteracy levels. While gender, occupation and total monthly income of respondents did not influence such levels, the study conclusively indicates that detachment from forest and natural resources is detrimental to the preservation and cultivation of ecoliteracy and that the connection of people and forests requires careful multidimensional attention.